Plant Disease Management: Leveraging on the Plant-Microbe-Soil Interface in the Biorational Use of Organic Amendments - Akanmu, Akinlolu Olalekan; Babalola, Olubukola Oluranti; Venturi, Vittorio; Ayilara, Modupe Stella; Adeleke, Bartholomew Saanu; Amoo, Adenike Eunice; Sobowale, Ayodele Adegboyega; Fadiji, Ayomide Emmanuel; Glick, Bernard R. (Frontiers in Plant Science, 2021)
Agriculture is faced with many challenges including loss of biodiversity, chemical contamination of soils, and plant pests and diseases, all of which can directly compromise plant productivity and health. In addition, inadequate agricultural practices which characterize conventional farming play a contributory role in the disruption of the plant-microbe and soil-plant interaction. This review discusses the role of organic amendments in the restoration of soil health and plant disease management. While the use of organic amendments in agriculture is not new, there is a lack of knowledge regarding its safe and proper deployment. Hence, a biorational approach of organic amendment use to achieve sustainable agricultural practices entails the deployment of botanicals, microbial pesticides, and organic minerals as organic amendments for attaining plant fitness and disease suppression. Here, the focus is on the rhizosphere microbial communities. The role of organic amendments in stimulating beneficial microbe quorum formation related to the host-plant-pathogen interactions, and its role in facilitating induced systemic resistance (ISR) and systemic acquired resistance (SAR) against diseases was evaluated. Organic amendments serve as soil conditioners, and their mechanism of action needs to be further elaborated to ensure food safety.